Pengaruh Pemberian Reward dan Punishment Terhadap Minat Belajar Bahasa Jerman Siswa-Siswi Kelas XI IBB SMAN 1 Tarik Sidoarjo - Panjaitan, Rachel Octavia; Pujosusanto, Ari (LATERNE, 2022)
The background in this scientific article is the lack of interest of students in learning German. The author finds a situation where students are less active and involved during the German language learning process even when the German language learning teacher has used various ways in delivering the material. Therefore, the purpose of this scientific article is to determine whether or not there is an effect of reward and punishment on students’ interest in learning German. The subjects observed in this scientific article are all 32 students of SMAN 1 Tarik Sidoarjo class XI-IBB for the academic year 2020/2021. The method applied in this scientific article is a qualitative with the purpose of understanding the phenomena experienced by the research subject and by describing the data obtained through words or sentences so that it can become a discourse which is the conclusion of the data analysis. Data collection for this scientific article used participatory observation where the researcher was directly involved during the German language learning process in the classroom using the observation sheet as the instrument. The results of this scientific article indicate that there is an effect of giving rewards on interest in learning while giving punishment does not affect students’ interest in learning.